2019
DOI: 10.1242/jcs.234781
|View full text |Cite
|
Sign up to set email alerts
|

Membrane trafficking as an active regulator of constitutively secreted cytokines

Abstract: Immune-cell activation by inflammatory stimuli triggers the transcription and translation of large amounts of cytokines. The transport of newly synthesized cytokines to the plasma membrane by vesicular trafficking can be rate-limiting for the production of these cytokines, and immune cells upregulate their exocytic machinery concomitantly with increased cytokine expression in order to cope with the increasing demand for trafficking. Whereas it is logical that trafficking is rate-limiting for regulated secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Regardless of the type of TP53 mutation, siRNA-mediated G55 depletion impaired the proliferative, colony-forming, migratory, and invasive activities of these cells draws from newly synthesized proteins, a conclusion supported by evidence that cycloheximide treatment decreased IGFBP2 levels in cell lysates and CM medium samples and abrogated ectopic G55-induced IGFBP2 secretion (Supplemental Figure 4A). To determine Proteins secreted by neuroendocrine and other secretory cells are stored in dense core vesicles that degranulate in response to external cues (21). However, by immunofluorescence staining, IGFBP2 and SPP1 did not localize in granules, which led us to speculate that secretion D-H).…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the type of TP53 mutation, siRNA-mediated G55 depletion impaired the proliferative, colony-forming, migratory, and invasive activities of these cells draws from newly synthesized proteins, a conclusion supported by evidence that cycloheximide treatment decreased IGFBP2 levels in cell lysates and CM medium samples and abrogated ectopic G55-induced IGFBP2 secretion (Supplemental Figure 4A). To determine Proteins secreted by neuroendocrine and other secretory cells are stored in dense core vesicles that degranulate in response to external cues (21). However, by immunofluorescence staining, IGFBP2 and SPP1 did not localize in granules, which led us to speculate that secretion D-H).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, elevated IL-6 gene expression did not translate into higher IL-6 protein as there was no difference in the amount of secreted IL-6 protein between groups ( Figure 5 C). IL-6 is a constitutively secreted protein that undergoes co-translational import into the endoplasmic reticulum, is trafficked to the Golgi complex, and then loaded into endosomes for transport to the plasma membrane [ 35 ]. In activated immune cells, the apparent bottleneck for cytokine secretion occurs during post-Golgi trafficking, which was the rate limiting step for cytokine release after pathogenic stimuli [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a constitutively secreted protein that undergoes co-translational import into the endoplasmic reticulum, is trafficked to the Golgi complex, and then loaded into endosomes for transport to the plasma membrane [ 35 ]. In activated immune cells, the apparent bottleneck for cytokine secretion occurs during post-Golgi trafficking, which was the rate limiting step for cytokine release after pathogenic stimuli [ 35 ]. While this mechanism has not been thoroughly investigated in RPE, the discrepancy between gene expression and the secreted IL-6 suggests a potential failure in either protein translation, processing, or trafficking to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism allows two advantages during infection: the expansion of macrophage membranes to engulf microbes and the specific delivery of tmTNF to a membrane structure enriched in TACE proteins (the phagocytic cup) where tmTNF is rapidly cleaved and released as active solTNF [ 52 ]. Importantly, a recent study suggested that intracellular TNF trafficking is rate-limiting for classical cytokine secretion in both macrophages and dendritic cells [ 53 ]. Like other constitutively secreted cytokines, TNF is able to self-regulate its secretion by signaling within recycling endosomes while in transit to the plasma membrane.…”
Section: Tnf Expression Signaling and Release From Microgliamentioning
confidence: 99%
“…Like other constitutively secreted cytokines, TNF is able to self-regulate its secretion by signaling within recycling endosomes while in transit to the plasma membrane. Once released, TNF can be endocytosed by cells and within the endocytic compartments can continue to signal inside recipient cells [ 53 ]. These regulatory mechanisms are important in immune cells, including microglia, for increasing cytokine production in response to pathogenic stimuli, or limiting it during tissue repair.…”
Section: Tnf Expression Signaling and Release From Microgliamentioning
confidence: 99%